Beyond dualism: Multisegmented labor markets in Ghana - James Heintz; Fabian Slonimczyk (University of Massachusetts, Department of Economics, 2007)
Using estimates of earnings functions in Ghana, this paper examines patterns of labor market segmentation with regard to formal and informal employment. Persistent earnings differentials are used as indicators of limited mobility across segments of the employed labor force. We find evidence of labor market segmentation between formal and informal employment and between different categories of informal employment which cannot be fully explained by human capital, physical asset, or credit market variables. We argue that dualist labor market models may not be appropriate for understanding employment dynamics in all circumstances and an approach that recognizes the multi-segmented character of labor markets may be preferable.
Keywords: J21; J30; O17; O55; 330; dualism; labor markets; employment; segmentation; Ghana